PENERAPAN PROBLEM BASED LEARNING PADA PEMBELAJARAN PENDIDIKAN KEWARGANEGARAAN UNTUK MENINGKATKAN HASIL BELAJAR SISWA KELAS IV - Ratna Dila Cahyaningsih; Aiman Faiz; Nurkholis; Rohiman (STKIP Subang, 2023)
The problem that occurs in the research carried out is the low learning outcomes of class IV students at SDN II Kalapagunung in the subject of Citizenship Education in the material of mutual cooperation or it can be said that there are still many students who have not met the criteria for achieving learning objectives, and learning has not been carried out more optimally. The research aims to improve the learning outcomes of Citizenship Education students by applying a Problem Based Learning (PBL). The type of research carried out was classroom action research with data collection instruments in the form of test questions and observations as supporting data. The analysis technique used is quantitative analysis technique. The research results show that the application of the Problem Based Learning (PBL) in the Citizenship Education subject on the material of mutual cooperation patterns can improve student learning outcomes. The percentage of completeness of student learning outcomes increased from cycle I to cycle II with a percentage of cycle I of 34% and increased to 100% or it can be said to be very good. Based on the results of this study, it was concluded that the Problem Based Learning (PBL) model could improve the learning outcomes of fourth grade students at SDN II Kalapagunung in the subject of Citizenship Education in the material of a mutual cooperation lifestyle. Thus, this model can be used as an alternative in learning Citizenship Education.